2019
DOI: 10.1016/j.juro.2018.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stereotactic Body Radiation Therapy for the Management of Oligometastatic Renal Cell Carcinoma

Abstract: SBRT can be considered a safe approach and provides effective local control of oligometastatic RCC. However future prospective studies are necessary to evaluate its impact on survival and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 1 publication
4
31
0
Order By: Relevance
“…Historically, RCC has been considered a radioresistant tumor but high radiation doses with BED >100 Gy could overcome this problem by offering other radiobiological models not yet sufficiently explored. Furthermore, high dose delivered in a few fractions could guarantee good local control as already demonstrated by the current retrospective study (22). SBRT treatment could be used in oligometastatic patients who are not candidates for radical surgery or as a non-invasive option of therapy.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Historically, RCC has been considered a radioresistant tumor but high radiation doses with BED >100 Gy could overcome this problem by offering other radiobiological models not yet sufficiently explored. Furthermore, high dose delivered in a few fractions could guarantee good local control as already demonstrated by the current retrospective study (22). SBRT treatment could be used in oligometastatic patients who are not candidates for radical surgery or as a non-invasive option of therapy.…”
supporting
confidence: 59%
“…In the recently published study by Franzese et al (22), local control and progression-free survival (PFS) rates at 18-month were 90.2% and 35%, respectively, while severe treatment-related toxicities were not observed. The authors aimed to analyze outcomes in terms of disease control and survival, and side effects.…”
mentioning
confidence: 98%
“…A locoregionally controlled primary tumour is not a precondition but should be considered a prognostic parameter which is critical to report specifically. Some studies reported a better prognosis for metachronous OMD [28,86], but this was not consistently observed [25,74]. Though both synchronous and metachronous metastases are considered OMD, the prognosis, options for treatment and risk of occult disseminated metastases of these patients can differ, with the length of the DFI appearing to have a prognostic impact [46,69,87].…”
Section: Oligo-progressionmentioning
confidence: 99%
“…Miller et al [54] demonstrated in the multivariate competing risks regression that concurrent first-line TKI treatment was independently associated with a local control benefit (HR 0.21, p = 0.04), while patients treated with TKIs alone experienced an increased rate of local failure (HR 2.43, p = 0.03). Franzese et al [55] showed in univariate and multivariable analyses that metachronous and single metastasis but non addition of target therapy predicted better progression-free survival. However, when the analysis was restricted to cells clear RCC cases only, target therapy performed before SBRT improved local control (HR 0.15, 95% CI 0.026-0.085, p = 0.032), suggesting different biological response of cell clear RCC to the combination of SBRT and targeted agents.…”
Section: Target Therapy and High Doses Rtmentioning
confidence: 99%